The role of arts engagement in reducing cognitive decline and improving quality of life in healthy older people: a systematic review - Massimo Fioranelli; Maria Grazia Roccia; Maria Luisa Garo (Frontiers in Psychology, 2023)
In recent years, arts engagement has been proposed as a non-pharmacological approach to reduce cognitive decline and increase well-being and quality of life in specific populations such as the elderly or patients with severe disease. The aim of this systematic review was to assess the effects of receptive or active arts engagement on reducing cognitive decline and improving quality of life and well-being in healthy populations, with a particular focus on the role of arts engagement in the long term. A comprehensive search strategy was conducted across four databases from February to March 2023. Ten studies with a total of 7,874 participants were incorporated in accordance with the PRISMA guidelines. Active and receptive arts engagement was found to be an effective approach to reduce cognitive decline and improve well-being and quality of life in healthy populations. The role of the positive effects of arts engagement could be determined by the combination of several factors such as exposure to cultural activities and the group effect. There is limited evidence of the protective effects of active arts engagement over a long period of time. Given the increasing demand for preventive programmes to reduce the negative effects of population ageing, more research on arts engagement should be conducted to identify its mechanisms and long-term effects.